2000
DOI: 10.1074/jbc.m005325200
|View full text |Cite
|
Sign up to set email alerts
|

Valine, Not Methionine, Is Amino Acid 106 in Human Cytosolic Thymidine Kinase (TK1)

Abstract: (t1 ⁄2 at 15°C is 41 and 392 min, respectively). Because valine with high probability is the naturally occurring amino acid at position 106 in human TK1 and because this position has high impact on the enzyme properties, the Val-106 form should be used in future investigations of recombinant human TK1.The human cytosolic thymidine kinase, TK1 (EC 2.7.1.21), is a key enzyme in the salvage synthesis of TMP from thymidine. Intracellular TMP is quickly phosphorylated to TDP and TTP. Because TTP is an allosteric ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
47
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 25 publications
11
47
0
Order By: Relevance
“…K m values were confirmed in a standard spectrophotometric assay (50) and an isothermal calorimetry assay that directly measures the heat of binding of the substrate to the enzyme and generated values of 27 and 24 M, respectively (P. F. Torrence and R. F. Smith, unpublished data). These values agree well with the reported value of 15 M for the human TK1 homolog purified from E. coli, which occurs predominantly as a dimer (4). These data suggested that the assay conditions were suitable for assessing the kinetic parameters of other potential substrates.…”
Section: Antiviral Activity and Tk Dependence In Orthopoxvirusessupporting
confidence: 82%
“…K m values were confirmed in a standard spectrophotometric assay (50) and an isothermal calorimetry assay that directly measures the heat of binding of the substrate to the enzyme and generated values of 27 and 24 M, respectively (P. F. Torrence and R. F. Smith, unpublished data). These values agree well with the reported value of 15 M for the human TK1 homolog purified from E. coli, which occurs predominantly as a dimer (4). These data suggested that the assay conditions were suitable for assessing the kinetic parameters of other potential substrates.…”
Section: Antiviral Activity and Tk Dependence In Orthopoxvirusessupporting
confidence: 82%
“…Amino acid 106 has been shown to have high impact on the enzymatic and oligomerization properties of TK1, with the valine 106 TK1 form behaving essentially as the endogenous TK1 (25,27). Comprehensive sequencing studies verify that valine is, in fact, the naturally occurring amino acid at site 106 (25,28,29). Expression and purification of TK1 was performed as described in ref.…”
Section: Methodsmentioning
confidence: 99%
“…24. LyTK1Val106 is derived from the tk1 gene from human lymphocytes (25), where codon 106 encodes a valine instead of a methionine as reported for the original tk1 clone (26). Amino acid 106 has been shown to have high impact on the enzymatic and oligomerization properties of TK1, with the valine 106 TK1 form behaving essentially as the endogenous TK1 (25,27).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 In addition, a modification of the sequence for TK1 has been described. 4 TK1, which is located in the cytoplasm, is a cell cycleregulated enzyme. 5 Its activity fluctuates with DNA synthesis, being high in dividing and malignant cells and low in quiescent cells.…”
mentioning
confidence: 99%